Histopathological Diagnostic Discordance between Punch Biopsies and Final Diagnostic Excisions of Cutaneous Squamous Cell Carcinoma: Analysis of 737 Cases - Katherine Hopkins; Åsa Ingvar; Johan Palmgren; Valdis Thorhallsdottir; Kari Nielsen; Karim Saleh (Acta Dermato-Venereologica, 2025)
The recommended treatment for cutaneous squamous cell carcinoma is surgical excision. An initial punch biopsy is often performed as an aid to diagnosis. A retrospective registry-based study was performed to assess histopathological concordance of punch biopsy of cutaneous squamous cell carcinoma and subsequent excision. Analysis of 737 punch biopsies and subsequent matched excisions was performed. In total, 493 (67%) lesions were confirmed as invasive cutaneous squamous cell carcinoma on excision, 76% when excluding “scar” as a final diagnosis. Tumour diameter > 20mm was highly predictive of cutaneous squamous cell carcinoma (positive predictive value 91.1%). Tumours on the scalp were significantly more likely to demonstrate a final diagnosis of cutaneous squamous cell carcinoma than those on the arm (odds ratio 6.11, 95% confidence interval 3.1,12.0). There was moderate concordance between biopsy and excision in grade of histopathological differentiation. This study demonstrates that clinical high-risk features may be of more value in predicting a diagnosis of cutaneous squamous cell carcinoma than partial punch biopsy. Use of clinical and dermoscopic competencies in assessment of cutaneous tumours rather than reliance on biopsies both avoids delay in patient management in the case of high-risk cutaneous squamous cell carcinoma and may also minimize unnecessary surgical excisions if there is a low clinical index of suspicion of cutaneous squamous cell carcinoma.